1997
DOI: 10.1080/07900629749863
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Management in Drought-prone Areas of Africa

Abstract: A BSTRACT The issues pertaining to groun dw ater droug ht are review ed w ith particular regard to the historical and present situations in M alaw i, northern G hana and the N orthern Province of So uth A frica. These three quite different exam ples highlight som e of the m ajor dif® culties facing respective governm ents and donor agencies, not least the shortcom ings of drought-relief drilling program m es,the general lack of routine m onitoring and the need for long er term ana lysis and assessm ent of grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 0 publications
4
56
0
Order By: Relevance
“…The reduction in groundwater recharge as depicted by the model results is consistent with the findings of [3] where they asserted that groundwater is a preferred source of water over surface water due to the high inter-annual variations in precipitation which tend to affect surface water availability. This is particularly the case in semi-arid environments in Africa and so is the case of the Olifants Basin [47]. A further investigation revealed that groundwater recharge constituted 3 -5% (ratios of 0.03 -0.05) of basin-wide mean annual precipitation (Table II).…”
Section: Impact Of Lulcc On Groundwater Rechargementioning
confidence: 86%
“…The reduction in groundwater recharge as depicted by the model results is consistent with the findings of [3] where they asserted that groundwater is a preferred source of water over surface water due to the high inter-annual variations in precipitation which tend to affect surface water availability. This is particularly the case in semi-arid environments in Africa and so is the case of the Olifants Basin [47]. A further investigation revealed that groundwater recharge constituted 3 -5% (ratios of 0.03 -0.05) of basin-wide mean annual precipitation (Table II).…”
Section: Impact Of Lulcc On Groundwater Rechargementioning
confidence: 86%
“…This increased demand is already observed in current climate variability, for example during droughts in southern Africa in the early 1990s (Calow et al, 1997) and more recently in the droughts in the Horn of Africa (MacDonald & Calow, 2007;Calow et al, 2009). In addition to these stresses, the ever-growing population across Africa puts considerable extra demands on individual sources.…”
Section: Increased Demand For Reliable Domestic Supplymentioning
confidence: 94%
“…Boreholes are therefore drilled not only in aquifers with high storage, but also in poorer aquifers, where storage is limited and recharge is required annually (or at least every 2 or 3 years) to maintain reasonable yields. Therefore, any reduction in annual rainfall, changes in intensity or seasonal variations may cause problems for water supply, particularly in aquifers with low storage capacity (Calow et al, 1997(Calow et al, , 2009.…”
Section: Estimating the Impact Of Changing Groundwater Recharge Patternsmentioning
confidence: 99%
“…In arid and semi-arid areas, groundwater resource is a sensitive factor of ecological environment [1][2][3][4], and helps to maintain vegetation in naturally occurring desert oases, as well as the social stability and economy in this desert environment [1,5]. Therefore, an accurate understanding of the spatiotemporal variability of groundwater is very important for making reasonable plans of oasis development and ensuring ecosystem sustainability [6].…”
Section: Introductionmentioning
confidence: 99%
“…The major objectives are (1) to analyze the spatial pattern and map groundwater level differences for the observation period; (2) to evaluate changes in the persistence of groundwater level differences with geostatistical methods; (3) to examine the temporal and spatial distribution trend in land cover by using historical remote sensing data; and (4) to explore the effect of land use change on groundwater depth.…”
Section: Introductionmentioning
confidence: 99%